Pernikahan Tidak Tercatat Dalam Perspektif Undang-Undang Perkawinan dan Akibat Hukumnya - Teuku Yudi Afrizal (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The Indonesian marriage laws postulate that a marriage is considered legal if it fulfilled all requirements that stipulates by the religion or faith that ones subscribed to; and it should be registered by the authority. Pernikahan Sirri is a kind of marriage which is considered illegal by the laws. Despites of its illegal status, the reality Indicates that it has been practiced widely with a different modus- operandi. In analyzing this issue, this article applies a legal normative approach that is by exploring literutres. It found that the Pernikahan Sirri has caused more demage to the marriage. As it is not legally registered, the wife and children were deprived of their legal rights to complain any time marriage break. The state acknowledges that the child of this married as illegitimate child who only has legal right related to the mother and her family. Consequently, they were deprived of their economic rights and joint assets of the marriage.